The call of the wild - London, Jack 1876-1916 (Portland House Illustrated Classics, 1987)
The adventures of an unusual dog, part St. Bernard, part Scotch shepherd, that is forcibly taken to the Klondike gold fields where he eventually becomes the leader of a wolf pack.